Influence of collective wine marketing on hungarian wine sector - Szakál, Zoltán (Acta Agraria Debreceniensis, 2008)
Nowadays, the importance of marketing is increasingly obvious. The number of those who apply those possibilities and methods provided by the marketing with which more efficient operation and higher amount of profit can be obtained is increasing. Special marketing fields have appeared that make the marketing characteristics of the single trades, product groups and industrial branches are widely known and utilized. During the more than 10 years following the changes of regime, the Hungarian wine market underwent a huge change. It is obvious, that this process has not stopped, and further market rearrangements may be claimed. The product and price policies have changed. Out of the marketing mix elements, mostly the marketing communication has changed, and the costumer has come to the centre. This marketing approach resulted in the formation of the newly established Hungarian Wine Marketing Public Benefit Company. The common marketing activity of the organization should have positive impacts on the industrial branch, although its efficient operation still has hindrances